Effect of Polyvinyl Pyrolidone on Morphology and Performance of Cellulose Acetate Based Dialysis Membrane - Waheed, H.; Hussain, A. (Engineering, Technology & Applied Science Research, 2019)
Polyvinyl pyrolidone (PVP) was added as filler in cellulose acetate (CA) to produce mixed matrix membrane (MMM) for hemodialysis operation. Phase separation induced by diffusion (DIPS) was used for fabrication of mixed matrix CA/PVP flat sheet membranes. The effect of adding PVP was investigated on the morphology and permeation efficiencies of CA membranes. The surface arrangement of polymer and additives in pure and blended membrane was studied by FTIR, contact angle and SEM. Results revealed homogenous and significant mixing of PVP content into pure CA matrix. Performance efficiency of blended membranes was investigated by means of pure water flux (PWF), urea clearance and % rejection of bovine serum albumin (BSA). The observable decrease of contact angle from 83° to 69° in CA/PVP MMM membranes of varying composition effectively revealed enhancement in hydrophilicity of MMM membrane surface. For protein rejection, all CA/PVP membranes rejected>90% of BSA relative to 25% for pure CA membrane. Furthermore, urea clearance behavior for CA/PVP membranes was 62.4% in comparison to 52% for pure CA membrane. The incorporation PVP i.e 1% by weight (Mpvp1) significantly improved the hydrophilicity, PWF, BSA rejection and urea clearance percentages of modified CA membrane for dialysis application.